2006
DOI: 10.1007/s10549-006-9428-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cytochrome P450 2D6 metabolism in women receiving adjuvant tamoxifen

Abstract: CYP2D6 metabolism, as measured by genetic variation and enzyme inhibition, is an independent predictor of breast cancer outcome in post-menopausal women receiving tamoxifen for early breast cancer. Determination of CYP2D6 genotype may be of value in selecting adjuvant hormonal therapy and it appears CYP2D6 inhibitors should be avoided in tamoxifen-treated women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
416
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(432 citation statements)
references
References 37 publications
8
416
0
8
Order By: Relevance
“…Although the present work has some limitations (the retrospective bias selection of patients, the sample size, the possible use of co-administered inhibitors and the infrequency of the CYP2D6 variants in the European population) our results clearly show a significant association between an absent or reduced enzyme function-homozygous or compound heterozygous for CYP2D6 alleles *4, *5, and *41-and worse disease-free survival. Benefits in event-free survival were similar to those found by Schroth and Goetz [14,15]. The fact that CYP2D6 poorer metabolizers have a worse clinical outcome than better metabolizers could be related to a reduced tamoxifen metabolism and lower endoxifen levels in the former; if we assume that a certain level of endoxifen is sufficient and necessary for tamoxifen efficacy, this level would not be reached by neither any CYP2D6 poor metabolizer nor by some of the patients with an intermediate metabolizer genotype.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Although the present work has some limitations (the retrospective bias selection of patients, the sample size, the possible use of co-administered inhibitors and the infrequency of the CYP2D6 variants in the European population) our results clearly show a significant association between an absent or reduced enzyme function-homozygous or compound heterozygous for CYP2D6 alleles *4, *5, and *41-and worse disease-free survival. Benefits in event-free survival were similar to those found by Schroth and Goetz [14,15]. The fact that CYP2D6 poorer metabolizers have a worse clinical outcome than better metabolizers could be related to a reduced tamoxifen metabolism and lower endoxifen levels in the former; if we assume that a certain level of endoxifen is sufficient and necessary for tamoxifen efficacy, this level would not be reached by neither any CYP2D6 poor metabolizer nor by some of the patients with an intermediate metabolizer genotype.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have evaluated the association between CYP2D6 genotype and clinical outcomes in women treated with adjuvant tamoxifen [11][12][13][14][15]. Two studies [14,15] retrospectively enrolled relatively homogeneous populations of patients who were estrogen-receptor positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15,21 At the clinical level, PM subjects with BC on adjuvant tamoxifen tend to have a higher risk of relapse. 22,23 This worse clinical outcome has been associated with a decreased prevalence of hot flashes, a putative marker of tamoxifen activity. 22 The findings have indicated that CYP2D6 genotype may be an independent predictor of tamoxifen efficacy in women with early BC.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with CYP2D6 extensive metabolizers, poor metabolizers exhibit a 3-fold higher risk of recurrence, 2,3 whereas CYP2D6 intermediate metabolizers (those with ''intermediate'' reductions in endoxifen concentrations) exhibit a lower risk of recurrence. [2][3][4][5] Given the characteristics of the study by Okishiro et al (median follow-up, 56 months among 173 patients, with 25% with the *10/*10 genotype; enrollment period, 6 years; follow-up, 4 years; and 5-year recurrence-free survival rate, 90% in the *10/*10 genotype subgroup), a 2-sided a ¼ .05 logrank test has a power of 26% to detect a 2-fold increase in the hazard of disease recurrence in the *10/*10 carriers relative to *10/wild type (wt) or wt/wt carriers.…”
mentioning
confidence: 99%